1996
DOI: 10.1289/ehp.96104s2299
|View full text |Cite
|
Sign up to set email alerts
|

Ethological and experimental approaches to behavior analysis: implications for ecotoxicology.

Abstract: Laboratory research in toxicology has progressed far beyond reliance on measures of mortality to make use of sophisticated behavioral preparations that can evaluate the consequences of sublethal toxicant exposure. In contrast, field studies have not evolved as rapidly. Approaches developed by experimental psychologists and ethologists provide powerful and complementary methodologies to the study of environmental pollutants and behavior. Observational data collection techniques can easily be used to broaden the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The older population is at greater risk for adverse health effects from extreme temperatures, susceptibility to disease, stresses on the food and water supply, and reduced ability to mobilize quickly (Geller & Zenick, 2005;Haq, Whiteleg, & Kohler, 2008). Older people also have heightened vulnerability to environmental threats such as exposure to neurotoxins and air pollution (Cohn & MacPhail, 1996;Stein, Schettler, Rohrer, & Valenti, 2008). Studies of the health impacts of extreme heat waves show greater effects on older people (Bouchama, 2004;Diaz et al, 2002;Klinenberg, 2002;McGeehin & Mirabelli, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The older population is at greater risk for adverse health effects from extreme temperatures, susceptibility to disease, stresses on the food and water supply, and reduced ability to mobilize quickly (Geller & Zenick, 2005;Haq, Whiteleg, & Kohler, 2008). Older people also have heightened vulnerability to environmental threats such as exposure to neurotoxins and air pollution (Cohn & MacPhail, 1996;Stein, Schettler, Rohrer, & Valenti, 2008). Studies of the health impacts of extreme heat waves show greater effects on older people (Bouchama, 2004;Diaz et al, 2002;Klinenberg, 2002;McGeehin & Mirabelli, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in social behavior observed in the present study are similar to changes observed in some of the animal models of autism (Crawley, 2007; Presti-Torres et al, 2007; Harmon et al, 2008, 2009). Overall, examining how toxicant exposure alters crucial natural behaviors using controlled laboratory techniques is very important in the developing field of ‘ecotoxicology’ (Cohn and MacPhail, 1996). This fusion of natural observation and experimentation could reveal important insights into behavioral dynamics of development and provide an understanding of the ways toxicants are harmful and ways to possibly prevent this harm.…”
Section: Discussionmentioning
confidence: 99%
“…Such training can be achieved through conditioned taste aversion (CTA). Conditioned taste aversion is a powerful innate response found across all vertebrates; an evolved defence mechanism against poisoning (Sinclair & Bird ; Conover ; Cohn & MacPhail ; Bernstein ; Mappes et al . ; Page & Ryan ; Glendinning ).…”
Section: Introductionmentioning
confidence: 99%